Potensi Dan Peluang UMKM Di Desa Batu Belubang, Kabupaten Bangka Tengah - Oktiansyah, Muhammad Ilham; Kurniawan, Edi; Andika, Rian; Lamora, Jhony Andrean; Saliman, Abdul Rasyid (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
For over three centuries, Kabupaten Bangka Tengah in the Bangka Belitung Islands Province has relied on tin mining and fisheries as the primary economic drivers. However, with shifting development priorities, the local government has begun to accelerate the growth of other sectors, including Micro, Small, and Medium Enterprises (MSMEs). As part of this effort, the Community Service Program (KKN) team from Universitas Pertiba Bangka Belitung conducted activities in Batu Belubang Village, Kecamatan Pangkalanbaru, aimed at exploring and enhancing the potential of local MSME products. Among these, Rusip Kering—a distinctive local product with significant potential but limited market recognition—stood out. Through educational programs and training focused on online marketing and packaging management, it is anticipated that MSME products like Rusip Kering can reach broader markets. This initiative is expected to positively impact the development of MSMEs in the village and contribute to the overall improvement of community welfare. This study underscores the importance of economic diversification in Kabupaten Bangka Tengah by developing the MSME sector as a new economic pillar for the region.